Analisis Pembelajaran Seni Rupa Dalam Kegiatan PMS MBKM di SMA Negeri 6 Kota Gorontalo - Hariana (Jurnal Ilmu Sosial Terapan, 2026)
This research aims to evaluate Fine Arts learning activities in Cultural Arts subjects at SMA Negeri 6 Gorontalo City in the Teaching Campus Program part of the MBKM Program.  The research method uses a qualitative descriptive approach to describe the learning situation at SMA Negeri 6 Gorontalo City, including learning quality, student motivation and creativity, student and teacher collaboration, challenges and solutions, long-term benefits, evaluation and reflection. The research data were collected through observation and observation, interviews, documentation, and direct participation in teaching and learning activities. This research involved PMS students from the Department of Fine Arts and Design, Cultural Arts Teachers, Students, and as supporters are all school residents of SMA Negeri 6 Gorntalo City. The results showed that there was an improvement in the quality of learning through theoretical and practical learning methods using a project approach. PMS students play an active role in improving the quality of the teaching and learning process through innovative learning, laboratory improvements, and collaboration with teachers. The positive impact of this activity is the increased quality of the teaching and learning process and student interest in the subject. The implementation of learning modules is very helpful for students in a planned and structured learning process.